भारतीय दर्शन को रुपरेखा - Hiriyanna, M. (Central Institute of Indian Languages Mysore, 2016)
Bharatiya Darshan ko Ruprekha gives an outline of the Indian philosophical traditions.
Bharatiya Darshan ko Ruprekha
Keywords: Nepali; भारतीय दर्शन; रुपरेखा; Bharatiya Darshan; Ruprekha; Philosophy; Nepali; Nepali